Pengaruh Disiplin Kerja, Motivasi Pegawai, dan Lingkungan Kerja terhadap Kinerja Pegawai di Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana (DP3AP2KB) Kota Batam - Afridariyana Afridariyana; Rini Elfina; Septa Diana Nabella (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study examines the influence of work discipline, employee motivation, and work environment on employee performance at the Office of Women Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) of Batam City. The research applies a quantitative approach with an associative design to determine the relationship and influence among variables. Data were collected from all employees using a structured questionnaire that had been tested for validity and reliability to ensure the accuracy of the research instrument. The analysis technique used is multiple linear regression to evaluate both partial and simultaneous effects of the independent variables on employee performance. The findings indicate that work discipline, motivation, and work environment collectively contribute significantly to improving employee performance. Individually, each variable also shows a meaningful and positive effect, reflecting the importance of both internal and external factors in shaping employee outcomes and productivity. These results imply that strengthening discipline, enhancing employee motivation, and creating a supportive, comfortable, and conducive work environment are essential strategies for improving organizational performance and achieving institutional goals effectively. Therefore, organizations are encouraged to implement policies and programs that support employee development, maintain a positive work atmosphere, and improve overall work quality in a sustainable manner.